Single-Shot Through-Focus Image Acquisition and Phase Retrieval From Chromatic Aberration and Multi-Angle Illumination - Zhou, Guocheng; Zhang, Shaohui; Zhai, Yayu; Hu, Yao; Hao, Qun (Frontiers in Physics, 2021)
Phase recovery from a stack of through-focus intensity images is an effective Non-interference quantitative phase imaging strategy. Nevertheless, the implementations of these methods are expensive and time-consuming, because the distance between each through-focus plane has to be guaranteed by precision mechanical moving devices, and the multiple images must be acquired sequentially. In this article, we propose a single-shot through-focus intensity image stack acquisition strategy without any precision movement. Isolated LED units are used to illuminate the sample in different colors from different angles. Due to the chromatic aberration characteristics of the objective, the color-channel defocus images on the theoretical imaging plane are mutually lateral shifted. By calculating the shift amount of each sub-image area in each color channel, the distances between each through-focus image can be obtained, which is critical parameters in the transport of intensity (TIE) and alternating projection (AP). At last, AP is used to recover the phase distribution and realize 3D localization of each part of the sample under test as an example. Both simulations and experiments are conducted to verify the feasibility of the proposed method.